Inflation expectations and the returns of growth and value stocks - Ramos, Martim Pita Silva (2022)
This paper examines the effect of inflation expectations and inflation surprises on growth and value stocks .Inflation is often identified as a major conditioning variable that influences future stock returns. Using a GARCH (1,1) model, I assess the impact of expected inflation produced by consumers and professional forecasters in two different periods: the period preceding the accommodative stance adopted by the Federal Reserve since the Great Financial Crisis and the period afterwards. Expected inflation produced by consumers depress monthly growth stock returns on average by close to 1% whereas the effect on value stocks’ returns varies between 0.5%and 0.7%, depending on the value criteria. Using professional forecasts, the negative impact on growth stock returns is reduced to close to 0.4% while the monthly decline in value returns is between 0.1% and 0.15%. Moreover, the results confirm that there was a significant change in the impact of expectations from the first to the second period, with growth stocks being significantly more impacted by higher inflation expectations than value stocks, mainly due to the role of monetary policy. The impact of inflation surprises is studied over the last 17 years, with the results suggesting that the impact of unexpected inflation is twice as high as the impact of expected inflation, depressing monthly returns by more than 2%.